Los betabloqueadores y su adecuado uso en pacientes con dislipidemia - Hernández Parets, Marleni; Armada Esmore, Zoila; Jiménez Fernández, Lisset; Hernández Hurtado, Estrella M. (CorSalud, 2013)
Los betabloqueadores y su adecuado uso en pacientes con dislipidemia